2018
DOI: 10.1590/1982-0216201820319417
|View full text |Cite
|
Sign up to set email alerts
|

Immediate effect of delayed auditory feedback on stuttering-like disfluencies

Abstract: Objective: to describe the immediate effects of delayed auditory feedback on stuttering-like disfluencies in people who stutter. Methods: a cross-sectional and experimental study. The effect of delayed auditory feedback was analyzed in thirty individuals, from eight to 46 years old, diagnosed with persistent developmental stuttering. Participants should present at least 3% of stuttering-like disfluencies and mild stuttering according to the Stuttering Severity Instrument. The following procedures were used: a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Results revealed that there was no significant decrease in most stuttering-like disfluencies except in word repetitions with the device in place when compared to no device. Design differences existed between Armson and Stuart [19] and Buzzeti and Oliveira's [20] investigations in comparison to other investigations that may have contributed to the differences in the results. First, the age of participants in Buzzeti's and Oliveira's [20] study were 8-46.11mos, whereas in other studies [14,15] the participants were adults.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…Results revealed that there was no significant decrease in most stuttering-like disfluencies except in word repetitions with the device in place when compared to no device. Design differences existed between Armson and Stuart [19] and Buzzeti and Oliveira's [20] investigations in comparison to other investigations that may have contributed to the differences in the results. First, the age of participants in Buzzeti's and Oliveira's [20] study were 8-46.11mos, whereas in other studies [14,15] the participants were adults.…”
Section: Introductionmentioning
confidence: 75%
“…Design differences existed between Armson and Stuart [19] and Buzzeti and Oliveira's [20] investigations in comparison to other investigations that may have contributed to the differences in the results. First, the age of participants in Buzzeti's and Oliveira's [20] study were 8-46.11mos, whereas in other studies [14,15] the participants were adults. Second, the condition examined in Armson's and Stuart's [19] investigation was frequency altered feedback whereas in other studies [9,14,15] both a delayed auditory feedback and frequency-altered feedback were investigated.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…A recent study of individuals with different stuttering severities showed that the delayed auditory feedback resulted in a reduction of word repetition frequency and articulatory speed, without impairing the flow of information. 40 …”
Section: Discussionmentioning
confidence: 99%